Endosome to Golgi Transport of Ricin Is Independent of Clathrin and of the Rab9- and Rab11-GTPases - Iversen, Tore-Geir (The American Society for Cell Biology, 2001)
The plant toxin ricin is transported to the Golgi and the endoplasmic reticulum before translocation to the cytosol where it inhibits protein synthesis. The toxin can therefore be used to investigate pathways leading to the Golgi apparatus. Except for the Rab9-mediated transport of mannose 6-phosphate receptors from endosomes to the trans-Golgi network (TGN), transport routes between endosomes and the Golgi apparatus are still poorly characterized. To investigate endosome to Golgi transport, we have used here a modified ricin molecule containing a tyrosine sulfation site and quantified incorporation of radioactive sulfate, a TGN modification. A tetracycline-inducible mutant Rab9S21N HeLa cell line was constructed and characterized to study whether Rab9 was involved in transport of ricin to the TGN and, if not, to further investigate the route used by ricin. Induced expression of Rab9S21N inhibited Golgi transport of mannose 6-phosphate receptors but did not affect the sulfation of ricin, suggesting that ricin is transported to the TGN via a Rab9-independent pathway. Moreover, because Rab11 is present in the endosomal recycling compartment and the TGN, studies of transient transfections with mutant Rab11 were performed. The results indicated that routing of ricin from endosomes to the TGN occurs by a Rab11-independent pathway. Finally, because clathrin has been implicated in early endosome to TGN transport, ricin transport was investigated in cells with inducible expression of antisense to clathrin heavy chain. Importantly, endosome to TGN transport (sulfation of endocytosed ricin) was unchanged when clathrin function was abolished. In conclusion, ricin is transported from endosomes to the Golgi apparatus by a Rab9-, Rab11-, and clathrin-independent pathway.